Non-fatal animal related injuries to youth occurring on farms in the United States, 1998 - Hendricks, K (BMJ Group, 2001)
Objective—To provide data on the magnitude and patterns of animal related on-farm injuries to youth in the United States. Data source—A survey of 26 000 farm households conducted for the National Institute for Occupational Safety and Health by the United States Department of Agriculture in 1998. Subjects—Youth younger than 20 years of age. Results—There were an estimated 6438 animal related on-farm injuries to youth in 1998. 70% occurred to farm residents; 69% were work related. Males accounted for 64% and approximately 41% occurred to those younger than 10; 37% involved horses and 31% cattle. Most horse related injuries occurred to females and a majority of the cattle related injuries were to males. Additionally, most of the cattle related injuries were work related, while horse related injuries were mainly non-work. Conclusions—One out of every five youth injuries occurring on farms in the United States is animal related. These animal related injuries were due to both work and non-work related exposures. The large number of horse and cattle related injuries highlights a need for intervention strategies based on the injury circumstances common to these animals.